The impact of aid on bureaucratic quality: does the mode of delivery matter? - Pablo Selaya; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2009)
We show that the impact of foreign aid on bureaucratic quality in recipient countries varies with the mode of delivery. Specifically, grants are found to impair the functioning of the bureaucracy, whereas loans are not. The negative impact of grants is larger when they are given as budget support rather than as assistance for specific projects or for programs in general.
Keywords: F35; 330; Foreign aid; bureaucratic quality; Entwicklungshilfe; OECD-Staaten-seitig; Wirtschaftspolitische Wirkungsanalyse; Bürokratie; Öffentliche Verwaltung; Dienstleistungsqualität; Entwicklungsländer